PENGARUH FEED RATE DAN DEEP OF CUT PROSES PERMESIN CNC ROUTER TERHADAP KEKASARAN PERMUKAAN AKRILIK - Putra, Muhammad Aldias; Anwar Sani, Almadora; Ismail, Iskandar; Sampurno, Rachmat D (MACHINERY Jurnal Teknologi Terapan, 2022)
Manufacturing machines are technologies that can help human work. One of them is the CNC router 3018. In the machining process of the CNC router, the level of surface roughness is one of the benchmarks for the quality of the resulting product. Departing from this problem, a tactic is needed in making machining parameter variables so that a good surface roughness value is obtained. The material used in this study is acrylic with a size of 70 Ã— 65 Ã— 5 mm, with a constant spindle speed of 1000 rpm, a variable feed rate of 200,300,400 mm/min and a varying depth of cut of 0.1,0,2,0.4 mm using a chisel made of tungsten carbide. One flute with a size of 3 mm. From the analysis that has been carried out, the lowest roughness level (Ra) is obtained under parameter conditions: spindle speed 1000 rpm, with a feed rate of 400 mm/min and a depth of cut 0.1 mm with a value of 0.654 m. the greatest value (Ra) is found at the spindle speed of 1000 rpm, with a feed rate of 300 and a deep of cut of 0.4 mm with a value of (Ra) 1,740 m, referring to the experiment using a variation of the feed rate, it was found that the relationship between the feed rate and the roughness value is negative with the equation y = -0.001x + 1.3634 this can be a reference in determining the value of surface roughness.